CHALLENGES OF GENDER MAINSTREAMING IN COLLABORATIVE TRANSNATIONAL RESEARCH - Mukashema, Immaculée; Bokore, Nimo; King, Regine; Husain, Abhar; McGrath, Susan (PEOPLE: International Journal of Social Sciences, 2019)
This paper addresses some of the challenges of gender mainstreaming in the context of a Rwanda-Canada social research project. The study partnership includes a team of academics from the Social Sciences Department at the University of Rwanda and three Canadian universities which are Calgary, St.Thomas and York. The ultimate goal of the research project is to create knowledge that could be used to train social workers to respond appropriately to the complex social issues of post-genocide Rwanda. The research team started by documenting the current practice of social work by Rwandan social workers; it wanted to be sure to understand the influence of indigenous cultures and values in social work practices. Interviews were conducted with 19 social work practitioners in Huye and Gisagara Districts of the Southern Province of Rwanda. The findings about the above stated goal have been published elsewhere. However, the present paper is focusing on the challenges of gender mainstreaming which arose after the field work. In this transnational social research project, the research team realized that it had not adequately addressed the different socio-cultural values of the researchers, particularly their understanding of gender and gender equality. It was found that when research team members/collaborators have different geopolitical locations, gender equal collaboration can be difficult to achieve. The paper reflects on the importance of research collaborators, either locally or transnational, to practice self-reflexivity as they negotiate the issues of power and privilege to produce non-hierarchical and accountable knowledge. The paper suggests that research team members need to be open to discuss the construction of gender and gender equality in both the local and the global context of the research. This research is a reminder that engaging gender throughout the process of transnational social research is crucial to addressing gender equity in post-conflict contexts.